Perilaku Petani Dalam Pengelolaan Usaha Tani Dengan Penerapan Teknologi Smart Farming 4.0 - Lina Asnamawati; Timbul Rasoki; Is Eka Herawati (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2020)
Lina A, Rasoki T, Herawati IE. 2020. Behavior of farmers in management of farming business with the implementation of smart farming 4.0 technology. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The application of technology to build a production process in agriculture so that the results of the agriculture are still running and sustainable. The research was conducted in Cikembulan Village, Kadungora District, Garut Regency. Farmers in Kadungora District are farmers who take advantage of the application of Smart Farming 4.0 technology in the form of using RITX Soil & Weather Sensor to record realtime land conditions and predict the weather. The research objective is to analyze farmer behavior; what factors can influence farmer behavior; the influence of farmer behavior in farming management with the application of smart farming technology 4.0 on the progress of their farming. This research design is a predictive and descriptive study involving several concepts. Descriptive analysis is expected to provide an explanation of the phenomenon of farmer behavior who applies this technology. The results of the analysis prove that the direct effect of the variable (genetic factors) to (farmer behavior in the application of smart farming) is -0.269, that it does not have a positive impact on the contrary reduces the behavior of farmers in the application of smart farming. The relationship between (individual external factors) is 0.392, namely, individual external factors have a positive impact in increasing farmer behavior in implementing smart fariming by 39.2%. to (Smart farming Technology Application Success Rate) has a direct effect of -0.108. The dependent variable, the indicator of Knowledge, Attitude, and Skills is quite significant in measuring the perception of the Y1 variable, namely 86.2%, 80.5%, and 78.2% respectively. As for, and being able to measure perceptions of 99.9% and 68.4%.